Between Merleau-Ponty and Ricoeur - Vinicio Busacchi (Critical Hermeneutics, 2023)
This paper aims to explore some aspects of Merleau-Ponty’s Phenomenology of perception (1945), proceeding from the chapter on attention – introductory section – to evaluate its redefining outcome, and to place it in dialectic with Paul Ricoeur’s research on Freedom and Nature (1950) – first section, chap. III. The hypothesis is that this work can help to shed new light both on a possible understanding of attention in the phenomenological perspective and that it can contribute to determine better the relationship between attention and the dimension of the involuntary. In the background, this opens up the dilemma about the possibility that a phenomenological approach to the unconscious could be a better explanation than a naturalising approach.